CSF-PCR in Diagnosis of Lyme Meningitis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
The sensitivity, specificity and predictive value of a Lyme CSF-PCR assay were evaluated in children from a Lyme-endemic region admitted to the Alfred I duPont Hospital for Children, Wilmington, DE, for suspected Lyme meningitis.